Karakteristik Ibu Bersalin Yang Mengalami Preeklamsia Di Rsud H.A Sulthan Daeng Radja Kabupaten Bulukumba - Ely Kurniati; Risnawati (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2017)
Childbirth is the process of spending conception results (fetus and uri) that has enough months (37 - 42 weeks) or can live outside the womb through the birth canal, then followed by the removal of the placenta and fetal membranes (Retnani, 2013). In childbirth mothers usually experience various difficulties, one of the complications is preeclampsia. Preeclampsia is a vasospastic disease, which involves many systems and is characterized by hemoconcentration, hypertension and proteinuria. Obese women before pregnancy have a greater risk of suffering from preeclampsia than normal women. Excessive weight gain during pregnancy can also increase the risk of preeclampsia in pregnant women. The purpose of this study was to determine the relationship between the Body Mass Index and the incidence of Preeclampsia in women giving birth in Bulukumba District in 2017.This study uses the Historical Cohort design. The sample in the study was selected with a Cluster Sampling method of 332 people. Data collection methods are carried out using Secondary data. Data were analyzed by univariate and bivariate analysis using Chi Square statistical tests. The results showed that P value = 0,000 (P <0,05) it was proven that the Body Mass Index was more significantly related to the incidence of Preeclampsia. It is expected that the results of this study can be used as a means of learning in an effort to broaden students' horizons regarding the incidence of preeclampsia in women who are related to the Body Mass Index and can be input for the District / City in following up on these problems by proclaiming programs in the city government, so they can reduce the incidence of Preeclampsia.